Effect of changes to the formal curriculum on medical students’ motivation towards learning: a prospective cohort study - Del-Ben, Cristina Marta; Shuhama, Rosana; Costa, Manuel João; Troncon, Luiz Ernesto de Almeida (São Paulo Medical Journal, 2019)
BACKGROUND: One of the factors known to influence performance in the learning process is student motivation. In turn, students’ motivation can be regulated by a large number of variables relating to the individual (such as sex, age and socioeconomic status) or to aspects of the academic life. OBJECTIVE: The primary aim of this study was to evaluate the influence of curriculum changes involving reduction in content overload and increased early exposure to clinical settings, on motivation towards learning among Year 1 medical students. Secondarily, the aim was to ascertain whether this influence on motivation remained stable until the undergraduate program ended (Year 6). DESIGN AND SETTING: Prospective study on two student cohorts at a Brazilian state-owned university. METHODS: Two consecutive student cohorts were assessed: one with a traditional curriculum (n = 87) and the other with a reformed curriculum (n = 63), at the same medical school. Participants in both co-horts gave responses on four scales in Years 1 and 6: the Academic Motivation Scale, containing sub-scales for autonomous and controlled motivation, and lack of motivation towards learning; Beck’s Anxiety and Depression Inventories; Spielberger’s State-Trait Anxiety Inventory; and the Social Adjustment Scale. In Year 6, 68% of the initial sample (66 students with the traditional curriculum and 36 with the reformed curriculum) was reassessed. RESULTS: No differences between Year 1 cohorts were found regarding demographic and social back-ground, social adjustment, depression or anxiety. Students with the reformed curriculum scored signifi-cantly higher regarding autonomous and controlled motivation than those with the traditional curric-ulum. Comparison between Year 6 and Year 1 showed increases in controlled motivation only for the traditional curriculum cohort. CONCLUSION: Curriculum changes were associated with increased motivation towards learning in Year 1, which persisted until Year 6.